2014
DOI: 10.1158/0008-5472.can-13-3225
|View full text |Cite
|
Sign up to set email alerts
|

API5 Confers Tumoral Immune Escape through FGF2-Dependent Cell Survival Pathway

Abstract: Identifying immune escape mechanisms used by tumors may define strategies to sensitize them to immunotherapies to which they are otherwise resistant. In this study, we show that the anti-apoptotic gene API5 acts as an immune escape gene in tumors by rendering them resistant to apoptosis triggered by tumor antigen-specific T cells. Its RNAi-mediated silencing in tumor cells expressing high levels of API5 restored antigen-specific immune sensitivity. Conversely, introducing API5 into API5low cells conferred immu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
67
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 25 publications
1
67
0
Order By: Relevance
“…The results analyzed by three different algorithms (NormFinder, BestKeeper, and geNorm) showed that apoptosis inhibitor 5 ( API5 ) was the best candidate reference gene for normalizing target gene expression in developing skeletal muscle across the tested prenatal and postnatal periods. API5 is highly conserved across species from microorganisms to plants and animals (Li et al, 2011; Mayank et al, 2015; Noh et al, 2014). AP15 has an important role in negative regulation of apoptotic processes in fibroblasts (Kim et al, 2000; Noh et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results analyzed by three different algorithms (NormFinder, BestKeeper, and geNorm) showed that apoptosis inhibitor 5 ( API5 ) was the best candidate reference gene for normalizing target gene expression in developing skeletal muscle across the tested prenatal and postnatal periods. API5 is highly conserved across species from microorganisms to plants and animals (Li et al, 2011; Mayank et al, 2015; Noh et al, 2014). AP15 has an important role in negative regulation of apoptotic processes in fibroblasts (Kim et al, 2000; Noh et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…API5 is highly conserved across species from microorganisms to plants and animals (Li et al, 2011; Mayank et al, 2015; Noh et al, 2014). AP15 has an important role in negative regulation of apoptotic processes in fibroblasts (Kim et al, 2000; Noh et al, 2014). This gene encodes an inhibitory protein that prevents apoptosis after growth factor deprivation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the aggressive nature of the defects leading to eBL development, downregulated miR-10a-5p could also promote the hyperactivation of API5 (apoptosis inhibitor 5), an apoptosis inhibitory protein, which renders tumor cells resistant to T cell initiated apoptosis (Noh et al, 2014). API5 has been shown to impair the cytotoxic effect induced by chemotherapeutic drugs (Faye and Poyet, 2010), while miR-10a-5p confers post-transcriptional regulation of API5 gene (Karginov and Hannon, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…353 Among them, the basic fibroblast growth factor 2 (FGF2), apart from carrying out its normal functions, also mediates tumor-induced angiogenesis and inhibits tumor cell apoptosis. [354][355][356] Further, the lack of a signal peptide makes FGF2 unique among its family members, and it is secreted into the extracellular space by an unconventional route, independent of ER/Golgi pathway. [357][358][359] In vitro studies suggest that the unconventional FGF2 translocation takes place through initial interactions with the inner leaflet PI(4,5)P 2 lipids.…”
Section: Fibroblast Growth Factor (Fgfs)mentioning
confidence: 99%